Antibacterial activity of intracanal medications based on calcium hydroxide and zinc oxide micro- or nanoparticles: an ex vivo study - Juliane Maria GUERREIRO-TANOMARU; Alana Priscila SOUZA AGUIAR; Gisselle Moraima CHÁVEZ-ANDRADE; Maria Inês Basso BERNARDI; Mário TANOMARU-FILHO (Universidade Estadual Paulista, 2017)
Abstract Introduction Nanoparticles and associations to calcium hydroxide can be used to increase antimicrobial activity. Objective To evaluate antibacterial activity against Enterococcus faecalis and pH of intracanal medications (IM) based on calcium hydroxide (CH) and zinc oxide (ZnO) micro- or nanoparticles, and their association with 0.4% chlorhexidine (CHX). Material and method Root canals from single-rooted human teeth were inoculated and incubated for 21 days. After sample (S1), the root canals were filled with the medications for 7 days and samples were collected immediately after medication (S2) and 7 days later (S3). Counting of CFU mL-1 was performed. Polyethylene tubes filled with the medications were used for the pH evaluation after 3, 7, 14 and 28 days. Data were submitted to ANOVA and Tukey tests (p<0.05). Result All IM promoted elimination of E. faecalis immediately after medication (S2). All the pastes promoted a similar pH increase. Conclusion CH/ZnO micro- or nanoparticles associated with CHX promoted greater bacterial reduction in the root canals and similar pH.